EFEKTIVITAS BENTUK LATIHAN SPRINTS 30 METER DI PASIR DAN 30 METER DI TANJAKAN TERHADAP POWER OTOT TUNGKAI - FIRDAUS, A.M. FARID PASYA; Wiriawan, Oce (Universitas Negeri Surabaya, 2022)
This study aims to determine the effectiveness of the form of sprint exercise in the sand group 1) or on an incline (group 2) as far as 30 meter to increase leg power. The method in this study is a quasi-experimental with a quantitative approach. By taking data from two groups of Pretest–Post-test design. The subjects of this study were 22 high school students in Nganjuk Regency. This study uses leg muscle power measurements with jumps without a prefix. The results of this study are group 1 pretest with the highest score of 3.15 meters and the lowest score of 2.5 meters. and for the post-test the highest value is 3.25 meters and the lowest is 2.7. Meanwhile, for groups, the highest value was 2.9 million and the lowest was 2.8 million. and for the post-test the highest value is 3.25 meters and the lowest is 2.8 meters. With the average development of group1 is 0.17 meters and group2 is 0.30 meters. The conclusion of this study is that both forms of exercise affect leg muscle power, group 1 is 6.09% and group 2 is 10.48%, so the effectiveness of the better form of exercise to increase leg muscle power from both types of exercise is the form of exercise Sprint 30 meters on an incline.